Translating research findings into educational policy and practice: the virtues and vices of a metaphor - Hammersley, Martyn (Nouveaux cahiers de la recherche en éducation, 2014)
A variety of metaphors have been used in seeking to conceptualise the relationship between social and educational research, on the one hand, and policymaking and practice, on the other. One influential analogy is the idea that research findings can and should be translatable into policy, and thereby into practice. This article will provide a conceptual analysis of the source meaning of «translation», and what is involved in this metaphorical use of it. It will be argued that many of the issues that arise in relation to translating text from one language into another have parallels in the task of communicating research findings to policymakers or practitioners. However, the idea that research findings can then be «translated» into policy and practice is much more problematic.